Experience of healthcare among the homeless and vulnerably housed a qualitative study: opportunities for equity-oriented health care - Eva Purkey; Meredith MacKenzie (BMC, 2019)
Abstract Background People experiencing homelessness are often marginalized and are known to face barriers to accessing acceptable and respectful healthcare services. This study examines the experience of accessing hospital-based services of persons experiencing homelessness or vulnerable housing in southeastern Ontario and considers the potential of Equity-Oriented Health Care (EOHC) as an approach to improving care. Methods Focus groups and in-depth interviews with people with lived experience of homelessness (n=31), as well as in-depth interviews of health and social service provider key informants (n=10) were combined with qualitative data from a survey of health and social service providers (n=136). Interview transcripts and written survey responses were analyzed using directed content analysis to examine experiences of people with lived experience of homelessness within the healthcare system. Results Healthcare services were experienced as stigmatizing and shaming particularly for patients with concurrent substance use. These negative experiences could lead to avoidance or abandonment of care. Despite supposed universality, participants felt that the healthcare system was not accountable to them or to other equity-seeking populations. Participants identified a system that was inflexible, designed for a perceived middle-class population, and that failed to take into account the needs and realities of equity-seeking groups. Finally, participants did identify positive healthcare interactions, highlighting the importance of care delivered with dignity, trust, and compassion. Conclusions The experiences of healthcare services among the homeless and vulnerably housed do not meet the standards of universally accessible patient-centered care. EOHC could provide a framework for changes to the healthcare system, creating a system that is more trauma-informed, equity-enhancing, and accessible to people experiencing homelessness, thus limiting identified barriers and negative experiences of care.